Koncepcja zdolności podatkowej i jej wpływ na kształt systemu podatkowego - Kośny, Marek (Concept of Fiscal Capacity and its Consequences for the Form of the Tax System, 2007)
The principle of fiscal capacity, strictly related to the concept of fiscal equity, postulates adjustments of tax burdens to the situation of the taxpayer. This adjustment takes into account two aspects of equity - principles of vertical and horizontal equity. The first one is concerned with growth of tax burdens along with increase in fiscal capacity. The second one postulates "equal treatment of equals". In terms of both principles, being a concretization of fiscal capacity principle, the aim of the paper is the analysis of their consequences for the shape of tax system. From the point of view of vertical equity there will be presented an analysis of the legitimacy of tax progression in the personal income tax. In the context of horizontal equity there will be made a trial of taking into account the taxpayers' family structure - that could be seen as one of the most important factors influencing fiscal capacity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 132-142